Preparation method of high-hardness super-smooth TiN coating
By combining vacuum sputtering and pure ion plating technologies with radio frequency sputtering and bent tube magnetic filters, a TiN coating with high hardness and low roughness was prepared, which solved the problem of insufficient performance of existing TiN coatings and achieved high-performance surface protection.
Patent Information
- Application Number
- CN202511490496.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-01-02
AI Technical Summary
Existing TiN coatings suffer from problems such as numerous surface particles, high roughness, low hardness, poor adhesion, and poor density, making it difficult to meet the industrial manufacturing demand for high-performance surface protective coatings.
TiN coatings were prepared by using vacuum sputtering and pure ion plating techniques, combined with radio frequency sputtering, bent tube magnetic filters and negative bias technology. By controlling the gas mixing ratio and ion cleaning, the ionization rate of Ti and N was improved, resulting in a dense and uniform TiN coating.
It significantly improves the hardness, brightness, and adhesion of TiN coatings, reduces surface roughness, and enhances coating density and bonding strength, thus meeting the requirements for high-performance surface protection.
Smart Images

Figure CN121250296A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating, specifically to a method for preparing a high-hardness, ultra-smooth TiN coating. Background Technology
[0002] TiN coating is a functional coating with high hardness, high wear resistance, and corrosion resistance, exhibiting a metallic luster. It is widely used for surface modification of materials in cutting tools, molds, and aerospace and marine industries. Currently, the main methods for preparing TiN coatings are sputtering and ion plating. However, existing preparation processes have the following shortcomings: ion plating produces TiN coatings with a high number of particles and droplets, resulting in high surface roughness; lower hardness leads to poor wear resistance and weak adhesion to substrates such as high-speed steel, resulting in a shorter coating lifespan; and insufficient density leads to poor wear resistance and corrosion resistance under strong external conditions.
[0003] To meet the increasing performance requirements of industrial manufacturing for surface protective coatings, it is necessary to provide a method for preparing high-hardness, ultra-smooth TiN coatings, which can further improve coating hardness, reduce surface droplets, reduce surface roughness, and improve the adhesion between the coating and the base material. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a high-hardness, ultra-smooth TiN coating, which can further improve the performance of the TiN coating.
[0005] The present invention is implemented in accordance with the following technical solution.
[0006] A method for preparing a high-hardness, ultra-smooth TiN coating, characterized by comprising the following operations: S10: Place the workpiece into the vacuum chamber, evacuate the vacuum chamber, and then introduce Ar to perform ion cleaning on the surface of the workpiece. S20: Cr and Ti layers are sequentially deposited on the workpiece surface using radio frequency sputtering technology; S30: A TiN layer is prepared on the surface of the workpiece using pure ion plating technology. During pure ion plating, a mixture of Ar and N gas is introduced into the vacuum chamber to assist in the ionization of the mixture in the vacuum chamber. A negative bias voltage is applied to the workpiece. An RF pulse power supply is used to improve the ionization rate of the Ti target. A bent tube magnetic filter is used to filter the ion beam.
[0007] The specific method is that the thickness of the TiN layer prepared in step S30 is 2-4 μm.
[0008] The thickness of the Cr layer prepared in step S20 is 0.1~0.5μm, the thickness of the Ti layer is 0.05~0.3μm, and the sum of the thicknesses of the Cr layer and the Ti layer is ≤0.6μm.
[0009] The RF pulse power supply used in step S30 has a pulse frequency of 16~20kHz, a base voltage of 50~200V, a peak voltage of 200~1000V, and a duty cycle of 50~95%.
[0010] In step S30, a coil is wound around the outside of the bent tube magnetic filter. The current connected to the coil is 0.5 to 35A, and the angle between the outlet and inlet of the bent tube magnetic filter is 22 to 90°.
[0011] In step S30, a mixture of N and Ar gas is introduced to make the pressure in the vacuum chamber 0.01 to 0.05 Pa, and the volume percentage of Ar in the mixture ranges from 50% to 90%.
[0012] In step S30, the power supply voltage used for auxiliary ionization is 100-2000V, the duty cycle is 50%-100%, and the generated ionization current ranges from 100 to 300mA.
[0013] In step S30, the negative bias voltage applied to the workpiece is 2.0 to 2.5 kV.
[0014] In step S20, during the radio frequency sputtering deposition, the current used to prepare the Cr layer is 4–10 A, and the current used to prepare the Ti layer is 2–8 A.
[0015] In step S10, Ar is introduced until the vacuum level in the vacuum chamber is 0.01 to 0.05 Pa. During ion cleaning, the cleaning power supply voltage range is 100 to 2000 V, and the cleaning time is 10 to 100 min.
[0016] The TiN coating prepared by the above method has a hardness that is consistently higher than 3000 HV, which is significantly and stably higher than the TiN coating prepared by the traditional ion plating process (2000~2500). The adhesion to the high-speed steel substrate is greater than 50 N, which is a significant improvement in the adhesion to the substrate. The prepared TiN coating has an N content of >45%, a high degree of ionization, good density, and a surface roughness Ra <10 nm. Attached Figure Description
[0017] Figure 1 This is a flow chart of the coating preparation process of the present invention.
[0018] Figure 2 This is a schematic diagram showing the hardness test results of the coating of the present invention.
[0019] Figure 3 This is a schematic diagram of the surface roughness detection results of the coating of the present invention.
[0020] Figure 4 This is a schematic diagram showing the surface morphology detection results of the coating prepared according to the present invention. Detailed Implementation
[0021] To make the objectives and advantages of this invention clearer, the invention will be specifically described below with reference to embodiments. It should be understood that the following text is merely used to describe one or more specific embodiments of the invention and does not strictly limit the scope of protection specifically claimed by the invention. Since sputtering coating and pure ion plating technologies have been developed for many years, the following description focuses only on the improved process. Some processing steps mentioned in the process of this invention, such as workpiece cleaning, sputtering coating, and pure ion plating, all have mature processes and can be referred to in existing industry operating procedures and processing methods.
[0022] Analysis of existing TiN coating preparation processes reveals the following direct reasons for the poor performance of TiN coatings.
[0023] 1. Existing ion plating technology uses excessively high energy when ionizing the target material with an electric arc. When generating Ti ions through arc discharge, neutral particles, ion clusters, and large particles are inevitably produced, which deposit on the product surface and form droplets, resulting in a rough coating surface. The deposition of various impurity particles prevents the TiN coating from forming a stable and continuous crystal structure, thereby reducing the coating's density and causing discontinuity in the crystal structure. This leads to increased internal stress, poor coating adhesion, shortened service life, reduced coating hardness, and weakened wear resistance.
[0024] 2. Existing ion plating processes involve relatively high pressures, approximately 0.1–0.5 Pa. This higher pressure necessitates the use of more N2 process gas, leading to adverse consequences. For example, the ionization rate of the gas decreases, reducing the effective collision rate between N and Ti ions. N ions lose more energy during their journey to the substrate surface, resulting in a lower energy level in the TiN coating and affecting its density. Higher pressures also introduce more impurities, impacting the coating's purity and metallic luster.
[0025] The technical solution adopted in this invention is as follows: Figure 1 As shown, the specific operations include the following.
[0026] Step 1: Place the workpiece in a vacuum chamber, evacuate to a base vacuum, and then introduce Ar to perform surface ion cleaning, removing surface impurities and oxide layers while reducing the surface energy of the workpiece.
[0027] The specific operation is as follows: Before being placed into the cavity, the workpiece needs to undergo one or more conventional treatments such as ultrasonic cleaning, surface polishing, and surface grinding to ensure sufficient cleanliness of the workpiece surface. The workpiece is placed and fixed in a clamp or fixing rod within the cavity, which is connected to the cavity chassis and can rotate with the chassis. The base vacuum is <0.0001 Pa to reduce impurities in the cavity gas and obtain a higher purity coating. Ar is introduced until the vacuum level reaches 0.01–0.05 Pa. Ion cleaning refers to the generation of Ar ions by voltage breakdown between the positive and negative electrodes of an ion power supply. The movement of Ar ions and their collision with the workpiece surface achieve the cleaning effect. The cleaning power supply voltage range is 100–2000 V, and the cleaning time for the workpiece surface is 10–100 min.
[0028] Step 2: A pure metal Cr layer and a Ti layer are sequentially deposited on the workpiece surface using radio frequency sputtering technology.
[0029] The specific operation is as follows: using pure metal Cr and Ti targets as sources, both with a purity of not less than 99.9%, first deposit a Cr layer on the workpiece surface and then deposit a Ti layer; the RF power supply current range used is 1 to 10 A, of which the current used for depositing the Cr layer is 4 to 10 A and the current used for the Ti layer is 2 to 8 A; the thickness of the deposited Cr layer is 0.1 to 0.5 μm and the thickness of the Ti layer is 0.05 to 0.3 μm, and the sum of the thicknesses of the Cr layer and the Ti layer does not exceed 0.6 μm.
[0030] Step 3: A TiN layer is prepared using pure ion plating technology. An RF pulse power supply is used to increase the ionization rate of Ti, and a bent-tube magnetic filter is used to filter out non-Ti ion atoms / groups, obtaining a high-energy pure Ti ion beam. A mixed gas of Ar and N is introduced, and partial Ar and N ions are obtained through power-assisted ionization. Bias voltage control technology is used to make Ar ions move towards the substrate and collide with N to generate N ions, further increasing the N ionization rate. Ti and N ions combine to form TiN, forming a continuous, uniform, and dense coating on the workpiece surface, characterized by high hardness, low roughness, high brightness, and high corrosion resistance.
[0031] The specific operation is as follows: a pure titanium target with a purity of not less than 99.99% is used as the source of Ti ions; the pulse power supply is used with a pulse frequency of 16~20kHz, a base voltage of 50~200V, a peak voltage of 200~1000V, and a duty cycle of 50%~95%. The pulse power supply can increase the energy density of Ti target ionization without increasing the power supply, resulting in Ti ion energy ranging from 30~50keV, far exceeding the 10~20keV of conventional multi-arc ion plating. High-energy Ti ions are more likely to form a stable and dense coating structure on the workpiece surface. A wound coil is installed outside the bent tube magnetic filter. The angle between the bend tube outlet and inlet ranges from 22~90°. A magnetic field is generated by applying a current of a certain magnitude to the wound coil, confining the Ti ions to move along the centerline of the bend tube into the cavity. The current applied to the coil ranges from 0.5~35A. A mixture of N and Ar gases is introduced to maintain a chamber pressure of 0.01–0.05 Pa; the volume percentage of Ar in the mixture ranges from 50% to 90% (the volume percentage refers to the gas percentage of the two gases in the vacuum chamber after introduction, the same below). Assisted ionization refers to breakdown ionization via voltage within the aforementioned vacuum range, using a power supply voltage of 100–2000 V, a duty cycle of 50%–100%, and an ionization current range of 100–300 mA. A negative bias voltage of 2.0–2.5 kV is applied to the workpiece. Applying this negative bias effectively attracts positively charged N and Ti ions to the workpiece surface, accelerating their migration and increasing ion energy to improve the deposition rate. The frequency is 16–20 kHz. N and Ti ions combine to form TiN, while Ar ions collide with unreacted N to generate new N ions. Simultaneously, Ar itself does not react with Ti ions and does not affect coating purity. The deposition temperature range is 100~150℃, which significantly reduces the temperature impact on the workpiece compared to conventional ion plating technology, where the surface temperature rise can reach 200℃ or even higher. The deposition process takes 2~10 hours, corresponding to a TiN coating thickness range of 1~5μm.
[0032] The TiN coating prepared by the above method has a hardness >3400HV, brightness L≥80, and roughness Ra<10nm. Under the condition that the workpiece material properties and shape and size are consistent, the coating has significantly improved the hardness (2500~3000HV), brightness (L70~75), and roughness (20~50nm) of the coating obtained by conventional preparation methods.
[0033] This invention has advantages over traditional preparation methods.
[0034] 1. Lower energy consumption. Using a pulsed radio frequency power supply as the energy source for generating Ti ions, the radio frequency pulse can effectively improve the ionization rate of Ti, reduce droplet formation, and at the same time reduce power consumption, thereby improving the energy utilization efficiency of the preparation process.
[0035] 2. Higher purity TiN coating. Utilizing bent-tube magnetic filtration technology, based on the principle that charged particles with a defined mass-to-nucleus ratio move along a specific path under the influence of Lorentz force in a magnetic field, a bent tube with a certain radius of rotation is designed. A coil is wound around the outside of the bent tube and direct current is applied to create an induced magnetic field. Ionized Ti ions can pass through, while atoms and ion clusters are absorbed by the bent tube wall, significantly improving the ionic purity of the deposited product surface. 3. TiN coating exhibits higher hardness. By introducing a small amount of argon gas and employing an ion-assisted ionization method to generate a small amount of Ar ions, and then using bias voltage control technology to allow Ar ions to collide with N gas to generate N ions, the ionization rate of N is further improved, thereby enhancing the density and hardness of the TiN coating. Simultaneously, Ar does not participate in the reaction and has no impact on the coating. The resulting coating is denser, has lower internal stress, and achieves a Vickers hardness of 3000~3300 HV (29~34 GPa), a significant improvement compared to traditional ion plating methods (2000~2500 HV).
[0036] 4. Improved TiN coating adhesion and surface smoothness. This invention removes large particles from traditional methods by using magnetic filtration and increasing nitrogen ionization rate, resulting in a denser TiN coating with better adhesion to the base material.
[0037] 5. The TiN coating exhibits a more pronounced metallic luster. Due to its denser coating, the surface roughness is lower, typically <10nm. Compared to traditional methods with a roughness generally greater than 15-20nm, this represents a significant improvement. Based on chromatograph results, the method of this invention achieves a coating brightness of 80, compared to only 75 achieved by conventional ion plating, demonstrating a significant improvement in brightness. Example
[0038] The pretreated and cleaned workpiece to be coated is placed in a vacuum chamber and fixed on a fixed rod inside the chamber. The fixed rod is directly connected to a turntable, which revolves at a speed of 10 r / min. The chamber is evacuated to a vacuum level of <1E-4 Pa using a vacuum pump set. Then, argon gas is introduced until the vacuum level reaches 0.03 Pa. The ion cleaning power supply is started, and the power supply voltage output is adjusted to 1000V~2000V, with a cleaning current of 55mA. Ionized Ar ions bombard the workpiece surface to achieve a cleaning effect. The cleaning time is 20 minutes.
[0039] After cleaning, the Ar gas intake in the chamber was changed to bring the chamber vacuum to 1 Pa. First, a pure metal Cr target was used, the sputtering power supply was turned on and the output current was set to 7 A, and the Cr layer thickness was 0.2 μm. Then, the Cr target was turned off and a Ti target was used. The sputtering power supply output current was adjusted to 4 A, and the Ti layer thickness was 0.1 μm.
[0040] After the Cr+Ti bottom layer structure was prepared, a mixture of Ar and N gases (85:15 ratio) was introduced to purge the chamber for 10 minutes, while simultaneously controlling the chamber vacuum to 0.05 Pa. The pulse power supply was started with a pulse frequency of 18 kHz, a base voltage of 150 V, a peak voltage of 250 V, and a base duty cycle of 85%. A 10 A DC current was applied to the coil wound around the outside of the bend, and the angle between the bend's outlet and inlet was 45°. The auxiliary ionization power supply was started with an output voltage of 1200 V, a duty cycle of 90%, and an auxiliary ionization current of 200 mA. A negative bias of 2.2 kV was applied to the turntable and the fixed rod, generating a bias current of 55 mA. Ti and N ions reacted to form TiN, which was deposited on the workpiece surface over a period of 5 hours.
[0041] The workpiece was removed, and the properties of the prepared coating were tested. Hardness was measured using a nano-hardness tester, gloss was measured using a chromatograph, and surface roughness was measured using a probe-type surface roughness meter. The surface hardness of the prepared TiN coating, measured using the nano-hardness tester, was >3100 HV (see appendix). Figure 2 The hardness of the TiN coating far exceeds that obtained by conventional ion plating methods. The surface brightness of the prepared TiN coating, measured by chromatography, is L=79.98. The surface roughness of the prepared workpiece, measured using a probe-type surface roughness meter, is only Ra 10 nm and Rz 84 nm (see appendix). Figure 3 The surface morphology of the workpiece was measured at 500x magnification using a scanning electron microscope (see attached image). Figure 4 ), indicating that it contains a very small number of droplets.
[0042] The above description is merely a preferred embodiment of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention. Structures, devices, and operating methods not specifically described or explained in this invention are implemented according to conventional methods in the art unless otherwise specified or limited.
Claims
1. A method for preparing a high-hardness, ultra-smooth TiN coating, characterized in that, This includes the following operations: S10: Place the workpiece into the vacuum chamber, evacuate the vacuum chamber, and then introduce Ar to perform ion cleaning on the surface of the workpiece. S20: Cr and Ti layers are sequentially deposited on the workpiece surface using radio frequency sputtering technology; S30: A TiN layer is prepared on the surface of the workpiece using pure ion plating technology. During pure ion plating, a mixture of Ar and N gas is introduced into the vacuum chamber to assist in the ionization of the mixture in the vacuum chamber. A negative bias voltage is applied to the workpiece. An RF pulse power supply is used to improve the ionization rate of the Ti target. A bent tube magnetic filter is used to filter the ion beam.
2. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, The thickness of the TiN layer prepared in step S30 is 2-4 μm.
3. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, The thickness of the Cr layer prepared in step S20 is 0.1~0.5μm, the thickness of the Ti layer is 0.05~0.3μm, and the sum of the thicknesses of the Cr layer and the Ti layer is ≤0.6μm.
4. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, The RF pulse power supply used in step S30 has a pulse frequency of 16~20kHz, a base voltage of 50~200V, a peak voltage of 200~1000V, and a duty cycle of 50~95%.
5. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, In step S30, a coil is wound around the outside of the bent tube magnetic filter. The current connected to the coil is 0.5 to 35A, and the angle between the outlet and inlet of the bent tube magnetic filter is 22 to 90°.
6. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, In step S30, a mixture of N and Ar gas is introduced to make the pressure in the vacuum chamber 0.01 to 0.05 Pa, and the volume percentage of Ar in the mixture ranges from 50% to 90%.
7. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, In step S30, the power supply voltage used for auxiliary ionization is 100-2000V, the duty cycle is 50%-100%, and the generated ionization current ranges from 100 to 300mA.
8. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, In step S30, the negative bias voltage applied to the workpiece is 2.0 to 2.5 kV.
9. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, In step S20, during the radio frequency sputtering deposition, the current used to prepare the Cr layer is 4–10 A, and the current used to prepare the Ti layer is 2–8 A.
10. The method for preparing a high-hardness, ultra-smooth TiN coating according to claim 1, characterized in that, In step S10, Ar is introduced until the vacuum level in the vacuum chamber is 0.01 to 0.05 Pa. During ion cleaning, the cleaning power supply voltage range is 100 to 2000 V, and the cleaning time is 10 to 100 min.
